Identification of antibiotic-resistant bacteria in activated sludge from a wastewater treatment plant in Tacloban City - Labitad, Patricia Isabel S.; Mallonga, Zoe K. (2024)
Antibiotic resistance poses a significant threat to global public health, as new resistance mechanisms continue to emerge and threaten the ability of healthcare professionals to treat infectious diseases. Bacteria that cause common infections like Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Streptococcus pneumoniae already have high resistance rates, Wastewater treatment plants (WWTPs) play a significant role in the spread of antibiotic resistance, acting as reservoirs for antibiotic-resistant bacteria (ARB) and antibiotic residues. This study aimed to characterize and identify bacteria that are resistant to ampicillin, chloramphenicol, gentamicin, kanamycin, and rifampicin, in activated sludge from a WWTP in Tacloban City. Twenty-six isolates were characterized, and a total of fourteen species were identified through molecular analysis. Seven of the identified species showed resistance to at least two antibiotics, specifically: Acinetobacter seohaensis and Aeromonas hydrophila to ampicillin and gentamicin; Enterobacter cloacae to chloramphenicol and gentamicin; Enterobacter hormaechei to ampicillin, chloramphenicol, gentamicin, and kanamycin; Enterococcus lemanii to kanamycin and rifampicin, Klebsiella pneumoniae to gentamicin and rifampicin; and Shigella flexneri to ampicillin, chloramphenicol, and kanamycin. The presence of ARB emphasizes the importance of enhancing WWTP systems to reduce the spread of ARB along with antibiotic-resistant genes (ARGs) for safeguarding public health and the environment.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.